De novo revertant fiber formation and therapy testing in a 3D culture model of Duchenne muscular dystrophy skeletal muscle. (15th September 2021) - Ebrahimi, Majid; Lad, Heta; Fusto, Aurora; Tiper, Yekaterina; Datye, Asiman; Nguyen, Christine T.; Jacques, Erik; Moyle, Louise A.; Nguyen, Thy; Musgrave, Brennen; Chávez-Madero, Carolina; Bigot, Anne; et al.
Abstract: The biological basis of Duchenne muscular dystrophy (DMD) pathology is only partially characterized and there are still few disease-modifying therapies available, therein underlying the value of strategies to model and study DMD. Dystrophin, the causative gene of DMD, is responsible for linking the cytoskeleton of muscle fibers to the extracellular matrix beyond the sarcolemma. We posited that disease-associated phenotypes not yet captured by two-dimensional culture methods would arise by generating multinucleated muscle cells within a three-dimensional (3D) extracellular matrix environment. Herein we report methods to produce 3D human skeletal muscle microtissues (hMMTs) using clonal, immortalized myoblast lines established from healthy and DMD donors. We also established protocols to evaluate immortalized hMMT self-organization and myotube maturation, as well as calcium handling, force generation, membrane stability (i.e., creatine kinase activity and Evans blue dye permeability) and contractile apparatus organization following electrical-stimulation. In examining hMMTs generated with a cell line wherein the dystrophin gene possessed a duplication of exon 2, we observed rare dystrophin-positive myotubes, which were not seen in 2D cultures. Further, we show that treating DMD hMMTs with a β1-integrin activating antibody, improves contractile apparatus maturation and stability. Hence, immortalized myoblast-derived DMD hMMTs offer a pre-clinical system with which to investigate the potential of duplicated exon skipping strategies and those that protect muscle cells from contraction-induced injury. Statement of Significance: Duchenne muscular dystrophy (DMD) is a progressive muscle-wasting disorder that is caused by mutation of the dystrophin gene. The biological basis of DMD pathology is only partially characterized and there is no cure for this fatal disease. Here we report a method to produce 3D human skeletal muscle microtissues (hMMTs) using immortalized human DMD and healthy myoblasts. Morphological and functional assessment revealed DMD-associated pathophysiology including impaired calcium handling and de novo formation of dystrophin-positive revertant muscle cells in immortalized DMD hMMTs harbouring an exon 2 duplication, a feature of many DMD patients that has not been recapitulated in culture prior to this report. We further demonstrate that this "DMD in a dish" system can be used as a pre-clinical assay to test a putative DMD therapeutic and study the mechanism of action. Graphical abstract: Image, graphical abstract